Hepatotoxicity of Titanium Dioxide Nanoparticles (TiO2-NPs) in Adult Albino Rat Model: Comparative Histolopathological Study - Sahib, Ahmad Hassan; Katia , Marwa Kadhim; Hassan, Sarah Satar (American Journal of Biomedicine and Pharmacy, 2025)
Oreview: Nanotechnology nanoparticles have seen noteworthy development in current years. This topic focuses on producing and applying nanoparticles (NPs) ranging in size from 1 near 100 nanometers. Titanium dioxide nanoparticles (Tio2-NP) are critical because of their numerous uses in a variability of biological and pharmaceutical fields and arrive the human body through several ways. Aim: Based on our data, few reserchs have examined the effects of titanium nanoparticles on the hepatic tissue. Consequently, this paper was planned to explore the conceivable pathologic effectiveness of titanium dioxide nanoparticles (TiO2-NPs) on hepatic tissue with reference to the histopathological, exploring the possible underlying processes and the expected degree of enhancement. Materials and Methods: The research project recruited a total of forty-two of healthy albino male rats to look into the impacts of titanium dioxide nanoparticles (TiO2-NPs). Throughout ten consecutive days, animals received TiO2-NPs in dosages of 50 µL or 100 µL, with tiny particles of 25 nm, 50 nm, and 75 nm. Results: Administration with TiO2-NPs exhibited substantial deviations in hepatocytes, portal triads, and sinusoids when compared with the untreated groups. The changes that has appeared in hepatocytes were prominently marked by hydropic and vacuolar degeneration, cytoplasmic hyaline inclusions, nuclear irregularities, binucleation, and evidence of nuclear damage for instance, karyolysis, karyorrhexis, and ultimate cellualr necrosis. Conclusions: All excpermental specimens who are subjected to TiO-NPs exhibit hepatocyte edema, predominantly as a consequence of decreased membranes functioning, consequential in an influx of water and (Na+) ions. This change promotes the release of lysosomal enzymes, which reasons cytoplasmic damage besides hydropic decline due to disrupted fluid and ionic equilibrium. The existence of vacuolated hepatocytes indicates damage to the liver, whereas binucleation represents cellular stress and an effort at renaissance. The damaging impact of TiO2-NPs, specifically the lesser particles, exacerbates hepatocyte damage via interfering with liver enzymes and antioxidant systems, producing reactive oxygen species that are (ROS), and increasing necrotic. More research is needed to entirely comprehend the potential therapeutic and investigative applications of TiO2-NPs.